2005
DOI: 10.1021/ja043289j
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Supramolecular Polymers Formed by Host−Guest Interactions

Abstract: alpha-Cyclodextrin with a p-t-butoxyaminocinnamoylamino group in the 3-position (3-p-(t)()BocCiNH-alpha-CD) has been found to form a supramolecular polymer in an aqueous solution. The degree of polymerization of the supramolecular polymer is higher than 15 at 20 mM, as proved by VPO (vapor pressure osmometry) measurements and turbo ion spray TOF MS measurements. The existence of substitution/substitution interactions between adjacent monomers of the supramolecular polymer have been confirmed by the observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
121
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(130 citation statements)
references
References 21 publications
1
121
0
3
Order By: Relevance
“…Among polyrotaxanes as one of the interlocked polymers (Figure 1), both poly [2]rotaxane [21][22][23][24][25][26][27][28][29][30][31][32][33] and poly [3]rotaxane 34,35 are specially unique as characterized by their structural feature that the polymer main chain has no successive covalent bond. The repeating units of these polymers are bound by mechanical bonds.…”
mentioning
confidence: 99%
“…Among polyrotaxanes as one of the interlocked polymers (Figure 1), both poly [2]rotaxane [21][22][23][24][25][26][27][28][29][30][31][32][33] and poly [3]rotaxane 34,35 are specially unique as characterized by their structural feature that the polymer main chain has no successive covalent bond. The repeating units of these polymers are bound by mechanical bonds.…”
mentioning
confidence: 99%
“…The nanoparticles were sunk inside and the height of the nanoparticles was about 0.8 nanometers, which was nearly the same height as one α-cyclodextrin. 30,31 The wall thickness of the sunk nanoparticles measured by AFM was about 20 nanometers ( Figure 3D). Both TEM and AFM images demonstrated that the blank polyrotaxane nanoparticles were hollow with vesicle-like morphology.…”
Section: Resultsmentioning
confidence: 99%
“…23 In this case, motion was triggered by solvent effects and not by photoisomerization processes, although the compounds contain stilbene groups. Harada and his team first showed that 6-cinnamamide-α-cyclodextrin and 6-aminocinnamate-α-cyclodextrin led to a doubly-threaded dimer.…”
mentioning
confidence: 94%